The Use Of DuPont System To Measure Profitability Performance (Case Research Cigarette Company On Listed Indonesia Stock Exchange 2008-2011) - Hartoko, Yoga Widya (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This research aims to know the trend analysis profitability perfomance byusing DuPont System in cigarette company. The data used in this research issecondary data. For assessing the perfomance of company financial condition, theresearch used time series analysis. Time series analysis provides the hints on howto evaluate by comparing the financial ratios of the company from one period toanother. It could be concluded that there have been different results of profitabilityperformance in each company. The highest results from DuPont System for fourconsecutive years from three companies were found in the Corner Indonesia StockExchange (IDX) Brawijaya University in Malang obtained PT HM SampoernaTbk.Keywords : DuPont System, Cigarette Company, Time Series Analysis.